Aluminium metallisation for interdigitated back-contact silicon heterojunction solar cells. (19th July 2017) - Stang, Johann-Christoph; Haschke, Jan; Mews, Mathias; Merkle, Agnes; Peibst, Robby; Rech, Bernd; Korte, Lars
Abstract: Back-contact silicon heterojunction solar cells with an efficiency of 22% were manufactured, featuring a simple aluminium metallisation directly on the doped amorphous silicon films. Both the open-circuit voltage and the fill factor heavily depend on the parameters of the annealing step after aluminium layer deposition. Using numerical device simulations and in accordance with the literature, we demonstrate that the changes in solar cell parameters with annealing can be explained by the formation of an aluminium silicide layer at temperatures as low as 150 °C, improving the contact resistance and thus enhancing the fill factor. Further annealing at higher temperatures initialises the crystallisation of the amorphous silicon layers, yielding even lower contact resistances, but also introduces more defects, diminishing the open-circuit voltage.